Dampak Keberagaman Gender Dewan Direksi dan Inovasi Lingkungan terhadap Biaya Utang di Indonesia - Aditia, Nugraha Calvin Marchellino; Kuang, Tan Ming (Politeknik Ganesha Medan, 2024)
This study aims to test and find out the influence of Board Gender Diversity and Environmental factors on the Cost of Debt of companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Using a quantitative method and a sample of 164 companies from various sectors, this research found that Board Gender Diversity does not have a significant influence on the Cost of Debt. This could be due to the still low level of gender diversity in the boards of directors of Indonesian companies, so its impact on debt costs is not yet clearly visible. Furthermore, the Environmental variable also does not have a significant influence on the Cost of Debt. Although environmental issues are becoming increasingly important, companies' awareness of disclosing related information is still low, so it has not yet impacted creditors' perceptions of company risk. The findings of this study can assist companies in developing more effective, sustainable corporate governance strategies and provide valuable information for investors and other stakeholders in assessing investment risks and opportunities.